Open to Feedback? Formal and Informal Recursivity in Creative Commons' Transnational Standard‐Setting. Issue 3 (11th September 2017) - Dobusch, Leonhard; Lang, Markus; Quack, Sigrid
Abstract: In this article, we examine how non‐membership organizations that claim stewardship over a transnational public or common good, such as the environmental or digital commons, develop combinations of formal and informal recursivity to develop and maintain regulatory conversations with their dispersed user communities. Based on a case study of Creative Commons, an organization that developed what have become the most widely used open licenses for digital content, we show how rhetorical openness to informal feedback from legitimacy communities in different sectors and countries can improve the feasibility and diffusion of standards. However, as long as the standard‐setter's methods of making decisions on the basis of such feedback remains opaque, its communities are likely to raise accountability demands for more extensive ex post justifications. Abstract : Rhetorical openness to informal feedback from legitimacy communities in different sectors and countries can improve the feasibility and diffusion of standards.